INFLUENCE OF MICROGEOMETRY OF CONTACT ON CHARACTERISTICS OF NON-ADHESION FRICTION OF SLIDING TRIBOSYSTEMS - Sydorenko О.U. (Proceedings of National Aviation University (archive), 2005)
Considered theoretical and experimental dependences specify influence of microgeometrical parameters of surfaces roughness of details, which were not taken into account earlier, on operational efficiency of unit of friction.